Pengukuran Survei Kepuasan Masyarakat (SKM) Dalam Pelayanan Publik Di Desa Masaran Kabupaten Sumenep - Wibisono, Aryo; Purnamasari, Mita; Suharsono, Agus; Pramesti, Wara (Wacana Equiliberium (Jurnal Pemikiran Penelitian Ekonomi), 2022)
This study aims to determine the perception and satisfaction of the community in public services in the village of Masaran, Sumenep district through the measurement of the Community Satisfaction Survey in terms of administrative services. The method used in this research is descriptive quantitative analysis using the Community Satisfaction Survey (SKM) based on the Regulation of the Minister of Administrative Reform and Bureaucratic Reform of the Republic of Indonesia No. 14 of 2017. This research was carried out in the village of Masaran, Sumenep Regency with a total of 100 respondents using a non-probability sampling technique with purposive sampling type. The data collected was carried out using a questionnaire or questionnaire method. The results of the study show that overall the services provided by the village of Masaran, Sumenep Regency are in the "Good" category with an SKM value of 3.42 and an SKM conversion value of 85.50. The steps taken by the village head in improving the quality of public services in the village of Masaran, Sumenep district are the first to pay attention to the dimensions of service quality and the second is to improve the quality of human resources.